Group Decisions, Between Competitive Motives and Knowledge Sharing : A Study on SME Groups in Malang District - Afwan Hariri Agus Prohimi; Lohana Juariyah; Syihabudhin Syihabudhin; Arief Noviarakhman Zagladi (Digital Innovation : International Journal of Management, 2024)
This research was conducted on UMKM groups established based on program instrumentation in the form of community development. The focus of this research is on the dynamics and processes that involve groups as strategic alliances between knowledge sharing and competitive motives. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews and focus group discussions. Identification of research informants was done by snowball sampling through key informants of group leaders and former group mentors. Triangulation of sources and methods was used to ensure the validity of the data. Field data will be collected, classified, reduced, and then interpreted according to the Miles and Huberman method. The group will be able to work and evolve if there is a reciprocal process of interests among its members, such as sharing knowledge. Between competitive motives and the process of sharing knowledge will potentially negate each other in group dynamics. Therefore, this dynamic requires factors that can ensure a balance between the two. How to keep competitive motives at a healthy competitive level and, on the other hand, not interfere with the process of sharing knowledge, which is one of the indicators that the group is working and developing.